FUNCTIONAL ANALYSIS AND TREATMENT OF PROBLEM BEHAVIOR IN EARLY EDUCATION CLASSROOMS1. Issue 1 (27th February 2013) - Greer, Brian D.; Neidert, Pamela L.; Dozier, Claudia L.; Payne, Steven W.; Zonneveld, Kimberley L. M.; Harper, Amy M.
Abstract We conducted functional analyses (FA) with 4 typically developing preschool children during ongoing classroom activities and evaluated treatments that were based on FA results. Results of each child's FA suggested social‐positive reinforcement functions, and differential reinforcement of alternative behavior plus time‐out was effective in decreasing problem behavior and increasing appropriate behavior. We discuss the utility of classroom‐based FAs and potential compromises to experimental control.